Employing Cloud Technologies in E-Learning Systems: University Students and Teachers' Ability in Storing Information in "Cloud": A "Google Classroom" Study - luqman qader (College of Education for Pure Sciences, 2020)
E-learning today has a significant impact on learning, due to its ease of accessibility and the fact that it does not take into account geography, politics, or narrow economic interests. This significance gains a special status, especially when having doubts regarding the possibility of a final settlement of the pandemic Coved-19 in a short period. Education using digital technologies allows students to expand their access to knowledge resources and to special skills which support the curriculum, as well as carrying using important features such as continuous assessments that enable them to advance in the field of research and to develop their ideas, and perhaps provide more opportunities to extend their knowledge and stimulate critical thinking that is formed by allowing students to gain knowledge and reach conclusions by themselves. With the spread of this huge number of smartphones, also of the availability of internet service at any time and place allows digital services to go beyond many boundaries to share information. "Cloud" computing technology provides optimal solutions for setting an effective infrastructure that allows researchers, teachers, and students to access services from anywhere and by using any kind of digital devices connected to the Internet to get valuable resources and services and to take advantage of the capabilities and functions provided by these modern environments. This contributes to providing the tools for supporting learning, teaching, and cooperative work. "Cloud" computing gives students and teachers a more convenient and effective learning experience.